2013
DOI: 10.1144/sp378.3
|View full text |Cite
|
Sign up to set email alerts
|

40 Ar/ 39 Ar Thermochronology on Central China Orogen: Cooling, uplift and implications for orogeny dynamics

Abstract: 40 Ar/ 39 Ar geochronology was carried out on the non-deformed synorogenic granitoid plutons from the Qinling-Dabie Orogen. The new model cooling history (MCH) method is applied to K-feldspar to obtain information about its cooling history. MCH is a quicker and easier method of calculating cooling histories compared with the multi-domain diffusion (MDD) model. Cooling histories indicate that Qinling-Dabie suffered differential uplift and denudation processes since the collision in the Late Triassic. East Qinli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 68 publications
2
3
0
1
Order By: Relevance
“…Sample 091128–1 presents a very distinct age spectrum pattern and a much younger maximum age (131.0 Ma) than the other five, suggesting that it has experienced a distinct cooling history. Its biotite age is similar to those of the postcollisional undeformed granites in the Dabie ultrahigh metamorphic belt (Zircon U‐Pb and biotite 40 Ar/ 39 Ar ages of 110–130 Ma) [ Zhao et al ., ; Wang et al ., ]. The pattern of the K‐feldspar age spectrum (Figure f) is also similar to those observed on the Dabie granites [ Wang et al ., ].…”
Section: Ar/39ar Geochronological Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Sample 091128–1 presents a very distinct age spectrum pattern and a much younger maximum age (131.0 Ma) than the other five, suggesting that it has experienced a distinct cooling history. Its biotite age is similar to those of the postcollisional undeformed granites in the Dabie ultrahigh metamorphic belt (Zircon U‐Pb and biotite 40 Ar/ 39 Ar ages of 110–130 Ma) [ Zhao et al ., ; Wang et al ., ]. The pattern of the K‐feldspar age spectrum (Figure f) is also similar to those observed on the Dabie granites [ Wang et al ., ].…”
Section: Ar/39ar Geochronological Resultssupporting
confidence: 81%
“…Its biotite age is similar to those of the postcollisional undeformed granites in the Dabie ultrahigh metamorphic belt (Zircon U‐Pb and biotite 40 Ar/ 39 Ar ages of 110–130 Ma) [ Zhao et al ., ; Wang et al ., ]. The pattern of the K‐feldspar age spectrum (Figure f) is also similar to those observed on the Dabie granites [ Wang et al ., ]. In addition, the nearby location (Figure ) also emphasizes a close relationship of the magmatic genesis between 091128–1 and those undeformed granites of the Late Mesozoic in Dabie.…”
Section: Ar/39ar Geochronological Resultssupporting
confidence: 81%
“…This requires a mechanism to thin the crust over a relatively short time period. Previous field and geochemical studies suggested that the SQB experienced rapid uplift and exhumation since ~210 Ma 30 , 48 , 49 . Magmatic activity decreased significantly after ~208 Ma as well and was dominated by volumetrically small and felsic plutonism indicating that mafic magmatic additions have contributed little to magma generation and crustal thickness (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…More low-temperature thermochronology results show that Daba Shan (Fig. 10a) (110 Ma;Tian et al, 2012;Li W et al, 2017), Qinling-Dabie Shan (110 Ma;Grimmer et al, 2002;Hu et al, 2006b;Heberer et al, 2014;Wang et al, 2015;Wang M et al, 2022), Mufu Shan (120 Ma;Lin et al, 2000;Ji et al, 2018;Shen et al, 2020), and Xuefeng Shan (100 Ma;Chu et al, 2020), as well as the eastern Sichuan Basin (100 Ma;Shi et al, 2016), experienced rapid exhumation again in the late Early Cretaceous. Therefore, the exhumation of the Huangling Massif was spatially synchronized with the aforementioned orogenic belts.…”
Section: Late Early Cretaceous Exhumationmentioning
confidence: 99%